Economic assessment of nutritional recommendations - Irz, Xavier; Leroy, Pascal; Requillart, Vincent; Soler, Louis-Georges (Toulouse School of Economics, 2014)
The effect of consumers’ compliance with nutritional recommendations is uncertain because of potentially complex substitutions. To lift this uncertainty, we adapt a model of consumer behaviour under rationing to the case of linear nutritional constraints. Dietary adjustments are thus derived from information on consumer preferences, consumption levels, and nutritional contents of foods. A calibration exercise simula tes, for different incomegroups, how the French diet would respond to various nutrition recommendations, and those behavioural adjustments are translated into health outcomes through the DIETRON epidemiological model. This allows for the ex-ante comparison of the efficiency, equity and health effects of ten nutritional recommendations. Although most recommendations impose significant taste costs on consumers,they are highly cost-effective, with the recommen dations targeting salt, saturated fat, and fruits and vegetables (F&V) ranking highest in terms of efficiency. A five percent change in consumption of any of those nutrients or food would reduce premature mortality in excess of 2100 lives annually. By contrast, urging consumers to modify their consumption of fibers, sugar-fat products and dietary cholesterol is unlikely to be socially desirable, often due to large unintended adjustments in some dimensions of dietary quality. Most recommendations are economically progressive, with the exception of that targeting F&V
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; diet; rationing; healthy; norms; food choice